The abolishment of death penalty as capital punishment: A comparative study of death penalty between Malaysia and Australia / Siti Adzlin Mohd Anwer … [et al.] - Yahya, Ahmad Hafiz; Md Hanafi, Muhammad Anas; Zunaidi, Muhammad Nazrul Anas; Mohd Anwer, Siti Adzlin (Faculty of Law, 2013)
Throughout the world, the subject of the relevancy of death penalty has become a polemic issue that will never be ceased from being debated unless all the countries in the world has finally come to a resolution that the imposition of death penalty should be completely abolished be it in law or in practice. Malaysia is among the nations that still preserve the imposition of death penalty in its criminal justice system. The method of execution is by hanging the criminals to death and a mandatory death sentence will be imposed towards the criminals who are guilty of the offence of discharging firearms at public, intentional murder and trafficking in dangerous drugs. While Malaysia is still practicing this gruesome law, most of the world's nations especially in the big part of Europe had already taken away this type of punishment from their laws. According to these 'civilised' nations, death penalty is a cruel punishment that denies the right to life of human beings. Besides, the punishment is being condemned for it is prone to establish unfairness and miscarriage of justice especially in a situation where an innocent man is being put to death and he will only be exonerated after several years of his execution. In order to know whether these arguments are valid and justified, a comparative study will be conducted between Malaysia and Australia. We choose to compare the law of Malaysia with Australia since both are applying common law principle.